Plasma IL-6 changes correlate to PD-1 inhibitor responses in NSCLC. Issue 2 (5th October 2020) - Keegan, Alissa; Ricciuti, Biagio; Garden, Padric; Cohen, Limor; Nishihara, Reiko; Adeni, Anika; Paweletz, Cloud; Supplee, Julianna; Jänne, Pasi A; Severgnini, Mariano; Awad, Mark M; Walt, David R
Abstract : Background: Blood-based biomarkers of anti-solid tumor immune checkpoint blockade (ICB) response are lacking. We hypothesized that changes in systemic cytokine levels with the initial doses of programmed cell death protein 1 (PD-1) pathway inhibitors would correlate with clinical responses. New ultrasensitive ELISA technology enables quantitation of plasma proteins in sub-picogram-per-milliliter concentrations. Methods: We measured plasma cytokines by ultrasensitive single-molecule array assays in patients with non-small-cell lung carcinoma before and during treatment with anti-PD-1 therapy. Association with best overall response and progression-free survival (PFS) was assessed by Kruskall-Wallis test and Kaplan-Meier plots with log-rank test, respectively. Results: A decrease in interleukin 6 (IL-6) levels was associated with improved PFS (n=47 patients, median PFS: 11 vs 4 months, HR 0.45 (95% CI 0.23 to 0.89), p=0.04). The extent of change in IL-6 differed between best overall response categories (p=0.01) and correlated with changes in C reactive protein levels. We also explored plasma cytokine levels in relation to immune-related adverse effects and observed some correlation. Conclusions: This study suggests the presence of a systemic, proteomic reflection of successful ICB outside the tumor microenvironment with plasma decreases in IL-6 and CRP.